Loneliness and physical activity: A systematic review. Issue 1 (1st January 2016) - Pels, Fabian; Kleinert, Jens
ABSTRACT: This article aims to provide an overview of the current state of research on the relationship between loneliness and physical activity (PA). A systematic literature search was conducted to identify all empirical studies assessing this relationship. A total of 37 studies stemming from 36 publications met the inclusion criteria. Study analyses comprised an individual consideration of each study and a systematic summarization of the studies. The majority of eligible studies focused on adolescent or elderly populations. Direct negative associations between PA and loneliness were found in half of the 24 cross-sectional studies. Of the seven identified longitudinal studies, one found a direct negative influence of PA on loneliness. Four longitudinal studies found evidence for a reverse influence, namely of loneliness on PA. Five intervention studies found PA to reduce loneliness. Two of the cross-sectional studies and one of the intervention studies found social support and social competence to moderate or to mediate the relationship between PA and loneliness. The findings indicate that PA can contribute to a decrease in loneliness. However, studies also indicate that any beneficial effect is dependent upon the quality of relationships present during physical activity. Additionally, loneliness itself might reduce the probability of being physically active.